Livelihood vulnerability index: Assessment of climatic changes in flood affected areas of Mianwali district, Punjab, Pakitan. - Afshin Akram; Arifa Tahir; Asifa Alam; Anum Waheed (PLoS ONE)
The world is facing substantial threats from climate change such as extreme weather events, floods, biodiversity loss, sea-level rise, and ecosystem degradation. The objective of this study is to assess the livelihood vulnerability index of communities in flood-prone areas, specifically investigating the reasons behind their vulnerability, their income sources, and the impact of flooding on economic activities. Pakistan is an agrarian country and known to be a climate vulnerable country, flood possess higher threat to rural livelihood. Mianwali district of Punjab, Pakistan was selected as the study area because it is among the poorest districts, and is most severely impacted district during 2010 catastrophe. The study employed qualitative methods like focus group discussions, interviews, and transect walks, alongside quantitative approaches such as the Livelihood Vulnerability Index (LVI). Primary data was collected from 200 households through structured questionnaires by applying simple random sampling technique. Results demonstrated that the overall vulnerability of the local community of Mianwali to flood was high 0.4 score (out of 5) as per Livelihood Vulnerability Index criteria. It was revealed that the exposure factor (0.424) significantly influenced vulnerability and communities had low adaptive capacity (0.077) in the face of flood hazard. While the sensitivity of Mianwali's community to flood scored 0.088. These findings are crucial for policymakers to assess baseline causes of livelihood vulnerability and formulate adaptation for other rural communities. It can be concluded that addressing these factors effectively in planning strategies may mitigate vulnerability and increase communities' capacity to deal with potential flooding.